Russia’s Long-Range Aviation: An Airborne Spear of the Nation - Muraviev, Alexey (Routledge, 2010)
In late 1999, Russia’s Long-Range Aviation (Dal’nia Aviatsia) celebrated its 85th Anniversary. On 15 December 1999, Commander-in-Chief of the Russian Fed- eration Air Force (RFAF), Colonel-General Anatoly Kornukov, issued an order to celebrate the Long-Range Aviation (LRA) Day on the 23 December each year.1 The airborne component of the Russian strategic deterrent forces (strategic bombers) traditionally appeared to be the least developed in terms of numerical strength, delivery capabilities and stockpile of nuclear warheads. Nevertheless, the Russian strategic bomber force was always at the center of attention of Western military and strategic experts and analysts.